Evaluation of patients with remission following radioactive iodine treatment: a retrospective analysis - Ooi, Cheow Peng; Kamaruddin, Nor Azmi (A S E A N Federation of Endocrine Societies, 2019)
Introduction: Prompt and appropriate management of thyrotoxicosis is important to prevent premature cardiovascular morbidity and mortality. In this respect, our experience with radioactive iodine therapy (RAI) has been very favourable with 85% achieving remission after six months. Nevertheless, the use of antithyroid drugs post-RAI has been suggested to be associated with hypothyroidism at one year. However, we do not use antithyroid drugs postRAI in our centre. We evaluated the characteristics of our patients who have remission after RAI.